(untitled) (Homoeopathy for All, 2022)
When we look at a person, what do we look at first? Obviously, eyes! Also when we speak to someone, we do not feel that the conversation is fruitful unless have good eye contact with that person. No wonder experts always give high priority to eyes when it comes to personal well-being. No one likes haggard, dull-looking eyes that reflect the internal ill-health. And therefore, one should take appropriate care of their eyes and enjoy various colours of life. Any serious trouble in connection with the eyes must always receive the most expert care and attention without any delay. There are, however, some eye conditions to which reference can be made here with advantage.